2019
DOI: 10.1101/561886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative investigation of factors relevant to the T cell spot test for tuberculosis infection in active tuberculosis

Abstract: 23Background 24 Previous qualitative studies suggested that the false negative rate of T cell spot test 25 for tuberculosis infection (T-SPOT.TB) is associated with many risk factors in 26 tuberculosis patients; However, more precise quantitative studies are not well known. 27 Objective 28 To investigate the factors affecting quantified T-SPOT.TB in patients with active 29 tuberculosis.30Methods 31 We retrospectively analyzed the data of 360 patients who met the inclusion criteria. 32 Using the lev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…A previous crosssectional study reported, 300 adult TB patients have surveyed China, they found that most male (90.8%) and female (58.4%) TB patients had insufficient daily protein intake. Li et al found that more TB patients had albumin levels <35 g/L (27). Our results showed that pulmonary TB with respiratory failure patients albumin levels were even lower, ≤30 g/L.…”
Section: Mortality Risk Factors Of Tb Patients With Respiratory Failure During Icu Treatmentsupporting
confidence: 44%
“…A previous crosssectional study reported, 300 adult TB patients have surveyed China, they found that most male (90.8%) and female (58.4%) TB patients had insufficient daily protein intake. Li et al found that more TB patients had albumin levels <35 g/L (27). Our results showed that pulmonary TB with respiratory failure patients albumin levels were even lower, ≤30 g/L.…”
Section: Mortality Risk Factors Of Tb Patients With Respiratory Failure During Icu Treatmentsupporting
confidence: 44%
“…A certain false negative rate had been found in IGRA among patients with tuberculosis especially in HIV infected individuals [8]. In addition, older age, non-Hispanic white race/ethnicity, being tested with T-SPOT.TB, albumin-globulin ratio, CD4+ and CD8+ had been think as the factors for TB-IGRA diagnosis in previous studies [8,9]. In HIV infected patients without active TB, TB-IGRA assay with MTB specific antigens were negatively correlated to numbers of circulating CD4+ T-cells, and was influenced by the degree of immunodeficiency [10].…”
Section: Introductionmentioning
confidence: 97%
“…The false negative of IGRA had been found in some TB patients especially combined HIV infection [8]. In addition, older age, non-Hispanic white race/ethnicity, being tested with T-SPOT.TB, albumin-globulin ratio, CD4 + T cell counts and CD8 + T cell counts had been thought as the in uencing factors of TB-IGRA diagnostic performance in previous studies [8,9]. In HIV infected patients, diagnostic performance of TB-IGRA(QFT-G-IT immune responses) was negatively correlated with circulating CD4 + T cell counts, and was in uenced by the degree of immunode ciency [10].…”
Section: Introductionmentioning
confidence: 99%